KASUS BULLYING PADA ANAK BERKEBUTUHAN KHUSUS: SYSTEMATIC LITERATURE REVIEW - Elma Diana; Marlina Marlina; Mega Iswari; Johandri Taufan; Rila Muspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying against Children with Special Needs (CSN) is a crucial issue in education, as it directly affects their psychological, social, and academic aspects. This study aims to systematically review the phenomenon of bullying among CSN, including its types, the roles involved, causal factors, impacts, and forms of intervention that have been implemented. Based on an initial search in the Scopus database, 1,646 articles were identified. After applying inclusion and exclusion criteria, 33 articles met the requirements for analysis. This research employed a Systematic Literature Review (SLR) approach combined with Bibliometric analysis (SLR+B), focusing on Scopus-indexed publications from 2010 to 2025. Data analysis was conducted using RStudio with the Bibliometrix and Biblioshiny packages to visualize research trends, author collaboration networks, and keyword mapping. The findings revealed that the most common forms of bullying experienced by CSN include physical bullying, verbal bullying, relational aggression, and cyberbullying. The parties involved consist of perpetrators, victims, bystanders, and neutral individuals, with the main contributing factors originating from family, school, peer groups, and media environments. The impact of bullying on CSN was found to be more severe than that on regular students, particularly in psychological, social, and academic domains. Interventions involving peer support proved effective in fostering inclusive school environments and reducing the incidence of bullying. This study provides significant contributions by presenting a comprehensive mapping of the latest literature, serving as a valuable foundation for educators, researchers, and policymakers in developing strategies for the prevention and management of bullying among children with special needs.